MATEMATIS (MALANG TEMATIK TOURISM): INOVASI DIGITAL MARKETING WISATA KAMPUNG TEMATIK BERBASIS PENTA-HELIX - Ida Ayu Githa Girindra (Jurnal Widya Publika, 2020)
The Indonesian tourism sector in 2014 has doubled since 2007 in contributing to the country's foreign exchange, amounting to USD 11,166.13 million. Malang City supports the Indonesian government in encouraging tourism growth, namely through the vision of 'Tri Bina Cita' with three main foundations, namely development. creative industry, education and tourism. Along with the development of thematic villages as leading tourism in Malang City, quoted from malangtoday.net, so far Malang branding is still considered less than optimal in terms of packaging, strategy and concept. This writing uses descriptive writing with a qualitative approach. The analysis technique used in this paper is SWOT. There is need for new innovations in increasing branding for thematic villages in Malang City, one of which is through the Mathematical program (Malang Thematic Tourism): Digital Marketing Innovation, Penta-Helix-Based Thematic Village Education Tourism in which there is tourism application used to increase branding village tourist attractions thematic in Malang City. The benefits of thematic village branding are in the form of: (1) Tri Bina Cita Malang City on one main foundations, namely tourism can contribute to support RI Law Number 23 of 2014, (2) Realizing Beautiful Malang city branding, (3) GRDP increases, ( 4) Expansion of employment